The Impact of Excessive Use of Electronic Games on the Emotional and Behavioral Balance of Children" A Field Study of Two Cases in Primary School" - Sayah, zouleykha (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study investigates the impact of excessive use of electronic games on the emotional and behavioral balance of primary school children, in light of the growing phenomenon of digital addiction among early childhood. The clinical approach was adopted as the most appropriate method to explore the psychological and behavioral dynamics related to this issue. The study focused on two cases of schoolchildren enrolled in a primary school in El Bayadh (Algeria), aged 10 and 11, who were intentionally selected due to the emergence of atypical emotional and behavioral indicators associated with excessive gaming. Data collection relied on three main tools: direct classroom observation to monitor daily interactions, semi-structured interviews with teachers and parents to identify emotional and behavioral changes, and a simplified questionnaire addressing the children’s daily digital habits. The findings revealed that excessive use of electronic games negatively affected the emotional balance of the children. Manifestations included increased levels of stress, heightened emotional reactivity, and difficulties in regulating anger outbursts. Furthermore, aggressive behaviors directed towards peers were observed, along with a noticeable decline in communication skills and social interaction within the school environment. These results suggest that excessive involvement in electronic gaming, particularly those containing violent or emotionally stimulating content, represents a critical factor contributing to the disruption of children’s emotional and behavioral development. Such patterns highlight the potential risks of digital overexposure for children’s psychological and social well-being during the primary school years.